The Use of 3D-CRT Technique in dose Distribution Analysis for Cervical Cancer Treatment Planning - An Nisa Octavia; Devina R. P. S. P; Robert Janssen Stevenly; Ave Kurnia Sari (LPPM Politeknik Aceh Selatan, 2025)
Three Dimensional Conformal Radiotherapy (3D-CRT) is a technique used in designing a cancer treatment (treatment planning system) using radiation emitted through a gantry with direction, angle, number of fields, and radiation energy according to needs. Determination of direction, angle, number of fields, and radiation energy precisely aims to provide effectiveness in cancer treatment. The purpose of this study was to determine the efficient use of multiple gantry angles in cervical cancer using a LINAC machine with 3D-CRT technique. Data processing in this study was carried out using quantitative analysis techniques, namely descriptive statistics. This analysis technique uses secondary data obtained from the results of the description that has been carried out by doctors at the Radiotherapy Installation. Data processing was carried out by carrying out a treatment planning system on 7 patients with each patient receiving planning using 4 gantry angles and 6 gantry angles. These results are visualized in the form of tables and graphs of absorbed doses received by patients. Based on this study, it can be concluded that using the 3D-CRT technique in cases of cervical cancer, using 4 gantry angles is more efficient than using 6 gantry angles.